Perceived Functions of Playfulness in Adult English as a Foreign Language Learners: An Exploratory Study - Barabadi, Elyas; Elahi Shirvan, Majid; Shahnama, Mojdeh; Proyer, René T. (Frontiers in Psychology, 2022)
Influenced by the flowering of positive psychology in the field of foreign language acquisition research in recent years, the present study aimed to explore the perceived functions of playfulness, as a personality construct, among English as a foreign language (EFL) learners. To this aim, a sample of 38 EFL learners were selected randomly from the private language institutes of Mashhad, the second largest city in Iran. They were interviewed about any perceived functions of playfulness in the EFL learning context. A qualitative content analysis of the collected data led to the extraction of four categories: Fun and laughter, creativity, mastery orientation, and cultivating relationships. A further in-depth analysis of the categories and comparison with the functions of adult playfulness in psychology (primarily Proyer’s 2014 and 2017 works of research) revealed that these four categories can be subsumed under two of the four structural components of adult playfulness; namely, other-directed playfulness and intellectual playfulness. The ability of EFL learners to turn language learning situations, tasks, and environment into enjoyable ones via their playfulness can have implications for the quality of their interpersonal interactions in class and eventually their language proficiency. The findings of this study can pave the way for the translation of the adult playfulness construct from developmental and personality psychology and family relations into the second language acquisition domain and its conceptualization in future research in this domain.